12t-15t=12

Simple and best practice solution for 12t-15t=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12t-15t=12 equation:


Simplifying
12t + -15t = 12

Combine like terms: 12t + -15t = -3t
-3t = 12

Solving
-3t = 12

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '-3'.
t = -4

Simplifying
t = -4

See similar equations:

| 8(4-u)+u=8tu | | x^2-18x+162=0 | | -5(2p+3)-27=3(3p+5) | | logx=log(x^2-12) | | -34+5y+9=2(4y-2)-3 | | 8bx-9ax=abc | | 7+6+4x-2(7x+6)=12x+40+2x | | 5t^2-26t=24 | | x^2-13x=-33 | | 2w^2-5w=3 | | 7x+9y=53 | | f=8.5+1.4(I-U) | | 8bx-9bx=abc | | -4+16=6b-1-5b | | a+8.25=22.5 | | 3(3n+3)=8(7n+5)+3 | | x=x^2-12 | | 3x-6=5-x | | 8=m+10 | | 3(x-6)+4=5(x+2)-12 | | -80z-0.4=-90z+1.7 | | 5x+7x=13 | | 109-(5x+12)=5(x+4)+x | | -180=-10(-3b) | | -5y-2=-4y-9 | | 6(4x-2)=108 | | 0.8+0.25t=0.6 | | 10-y=2x-3 | | x+5(x+2)=40 | | 04+0.33t=0.2 | | (x+2)(x-5)=2-2x | | a+26.5=42 |

Equations solver categories